SPEECH ACTS IN SURAH AL-FÂTIHAH: A Pragmatic Analysis from the Perspective of Speech Act Theory - Audrya Fauzi Islami; Ade Nandang (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Surah Al-Fâtihah occupies a central role in Islamic prayer and requires an understanding that extends beyond syntactic interpretation to the pragmatic dimensions of the text. This study aims to examine the types of speech acts, the distribution of illocutionary acts, and the theological-pragmatic implications embedded in the seven opening verses of the Qur'an. A descriptive qualitative method was employed using a textual analysis approach based on John R. Searle's taxonomy of illocutionary acts. The findings indicate that Surah Al-Fâtihah exhibits a complex configuration of speech acts. The first four verses are predominantly characterized by assertive and expressive illocutionary acts, which construct an acknowledgment of divine reality while simultaneously expressing gratitude and complete submission to God. The fifth verse represents the strongest manifestation of commissive speech acts through an exclusive commitment to worship Allah alone. In contrast, the sixth and seventh verses are dominated by directive speech acts expressed through earnest supplications for divine guidance and protection. The theological-pragmatic implications of these findings suggest that the recitation of Surah Al-Fâtihah in prayer functions as a form of sacred speech act and ritual performativity. The asymmetrical relationship between human beings and God transforms language from a medium of information exchange into a performative act that continuously reinforces spiritual commitment and facilitates the purification of the self.